2001
DOI: 10.3354/meps211245
|View full text |Cite
|
Sign up to set email alerts
|

Identification of riverine, estuarine, and coastal contingents of Hudson River striped bass based upon otolith elemental fingerprints

Abstract: Elemental fingerprints of otoliths from Hudson River striped bass Morone saxatilis were used to define resident, estuarine, and ocean migratory contingents, which had previously been determined by otolith microprobe analysis of Sr:Ca. Using solution-based inductively coupled plasma mass-spectrometry, 7 metals were quantified in whole otoliths. Discriminant analysis of elements showed a high degree of separation among the 3 migratory contingents. Barium was significantly higher in otoliths from the freshwater r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 39 publications
4
88
0
Order By: Relevance
“…Researchers have primarily used Sr : Ca (Secor et al 1995;Fablet et al 2007;Hedger et al 2008) and, to a lesser extent, Ba : Ca (Elsdon and Gillanders 2005a;Hamer et al 2006) ratios, to reconstruct environmental histories of fish based on the relationships that they form with salinity. We found that the relationship between salinity and either Sr : Ca or Ba : Ca was not simple, and therefore it is difficult to use these simple single-element relationships to reconstruct environmental histories of hardyhead in the Coorong.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have primarily used Sr : Ca (Secor et al 1995;Fablet et al 2007;Hedger et al 2008) and, to a lesser extent, Ba : Ca (Elsdon and Gillanders 2005a;Hamer et al 2006) ratios, to reconstruct environmental histories of fish based on the relationships that they form with salinity. We found that the relationship between salinity and either Sr : Ca or Ba : Ca was not simple, and therefore it is difficult to use these simple single-element relationships to reconstruct environmental histories of hardyhead in the Coorong.…”
Section: Discussionmentioning
confidence: 99%
“…Fish migrate in order to optimize life-history stages that may require specific environments, or to take advantage of a condition offered by the different water type and/or habitat, such as increased food resources or shelter (Limburg 2001;Secor et al 2001). Traditional approaches to determining fish movement have involved conventional tags (e.g., dart tags) or, more recently, acoustic and radio tags.…”
mentioning
confidence: 99%
“…Previous research on northern stocks of Striped Bass has provided evidence for diverse lifetime migration patterns: some members of a given population reside in freshwater or estuarine environments throughout their life (resident contingent) and others are more exploratory and engage in large-scale coastal migrations (migratory contingent) (Clark, 1968;Secor, 1999). There is particularly strong evidence for this "contingent" behavior in Striped Bass in the Hudson River (Secor and Piccoli, 1996;Secor et al, 2001;Zlokovitz et al, 2003). Our study, however, provides little indication of this phenomenon in the AR stock of Striped Bass.…”
Section: Effects Of Fi Sh Size On Recapture Areamentioning
confidence: 99%
“…Our use-groups were similar to spawning and migratory contingents (Clark 1968;Secor et al 2001) originally defined by Clark (1968) as a unique group of striped bass that ''engage in a common pattern of seasonal migrations between feeding areas, wintering areas, and spawning areas.'' Within contingents, migratory shifts occur, suggesting that these designations need not remain static over the life of the fish (Wingate and Secor 2007).…”
Section: Use-groups (Foraging Contingents)mentioning
confidence: 99%